Effects of glass fiber reinforced polymer pipe waste powder usage on concrete properties - Saribiyik, Ali; Gurbuz, Guven (Revista de la Construcción. Journal of Construction, 2021)
<span style="font-size: 10.0pt; line-height: 107%; font-family: ’Times New Roman’,serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">In this study, the recycling of pipe waste powder in concrete has been experimentally investigated to reduce its harm to the environment and human health. Glass fiber reinforced polymer pipe waste powder (GFRP-WP) reveals during the production of additional coupling and bends of GFRP pipes produced for clean water and wastewater systems. GFRP-WP is composed of polyester resin, sand, and E-glass fiber. GFRP-WP was used as a partial replacement to fine aggregate in proportions of 0% 5%, 10%, 20%, 30% and 40% to the concrete mixture. The effect of GFRP-WP was examined on the physical and mechanical properties of concrete, such as compressive strength, workability, capillarity, and water absorption. According to the results, it was seen that GFRP-WP could be used as filler in concrete, and some positive and negative effects on concrete were also determined. GFRP-WP reduced the workability of concrete. Therefore, GFRP-WP impaired the properties of the concrete if certain mixing ratios were exceeded. It was determined that GFRP-WP could be used in concrete up to 15% by volume as a partial replacement for fine aggregate. <!– [if gte mso 9]> acer 15.00 <![endif]–><!– [if gte mso 9]> Normal 0 21 false false false TR X-NONE X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>